Deconstructing aspects of native speakerism: Reflections from in-service teacher education - Hall, Stephen J. * (Asian Association of Teachers of English as a Foreign Language., 2012)
In many Asian contexts, issues of who teaches and educates teachers in English Language Teaching remain challenging with status accorded to socalled ‘native speakers’. Issues still remain after two decades of research calling for deconstruction of the native speaker fallacy. Drawing on critiques of the concept, as well as teacher education research, this paper suggests ways to deconstruct the maze of native speakerism. Recent Malaysian in- service training research shows that positioning and modeling can override the origin of the teacher educator, namely a so-called native speaker background. Descriptions of techniques to help deconstruct native speakerism at the interactional level are derived from teacher educator reflection on data. Possibilities for countering native speakerism are suggested through descriptions of how teacher educators may model and use humour to address perceptions of hierarchy. With the growing use of English as an additional language, research into who teaches or educates teachers could also address the challenges of hidden professional racism sustained by factors such as so-called Standard English. Practical approaches from teacher educator reflections on their interaction with Malaysian teachers suggest ways to reconstruct aspects of native speakerism.